Immune Modulation and CMV Reactivation In Sepsis-Induced Immunosuppression. (28th October 2020) - Lambe, G R; Kapadia, F N; Khodaiji, S; Rodrigues, C
Abstract: Introduction/Objective: Sepsis is a global health priority and is often accompanied by a transient immune paralysis, associated with impairment in innate and adaptive immunity leading to progressive immunosuppression and higher susceptibility to secondary infections. Reactivation of Cytomegalovirus (CMV) occurs frequently and has been associated with adverse outcomes even in immunocompetent patients, with sepsis. Study objective was to evaluate the association between incidence of CMV reactivation and immune alteration in sepsis-induced immunosuppression in patients with prolonged sepsis. Methods: Prospective observational study, which included consecutive patients admitted to hospital ICU, with severe sepsis and length of stay > 48 hours. Patients with other causes of immune-suppression and anti-CMV treatment were excluded. Blood samples were collected on enrolment and further weekly until 21 days or death/discharge. Quantification of CMV viremia was done using RT-PCR (qPCR). Markers used to evaluate immune suppression using Flow Cytometry were i) lymphocyte subsets (CD3+, CD19+, CD16+CD56+, CD4+, CD8+ and regulatory T cells - CD25+ CD127-), ii) surface receptor expression of HLA-DR on monocytes, and Programmed Death marker expression (PD-1) on T lymphocyte, iii) Measurement of pro-inflammatory(IL-6, TNF-a, IFN-g) and anti-inflammatory cytokines(IL-4, IL-10) by Cytometric Bead Array (CBA) assay. Results: A total of 25 CMV IgG positive patients and 11 healthy controls were analyzed. CMV reactivation occurred in 20 patients. Median time for reactivation was 7 days. Patients with CMV reactivation had significant T-cell lymphopenia (p<0.01). PD-1 expression on both CD4+ and CD8+ T cells in these patients was markedly elevated as compared to non-reactive group. HLA-DR expression was significantly low on monocytes in all sepsis patients (p<0.01) vs healthy controls; however it did not show any significant correlation. Levels of IL-6 showed marked elevation from day 7 while, IL-10 was observed to be significantly higher from day 0 in CMV reactivated group as compared to the CMV non-reactive group of patients. Conclusion: Our study evidence suggests that monitoring lymphocyte subsets, PD-1expression on T lymphocyte, and levels of IL-6/IL-10 using flow cytometry, may serve as indicators for reactivation of CMV. Individualized immune therapy such as PD-1 receptor blockade drugs can be used to optimize treatment of patients with severe sepsis.